Successful management of injuries to the portal triad: A 2019 EAST master class video presentation. Issue 1 (July 2019) - Coleman, K. Conley; Warner, Rachel L.; Bardes, James M.; Wilson, Alison; Inaba, Kenji; Borgstrom, David; Marsh, J. Wallis; Grabo, Daniel J.
Abstract : Supplemental digital content is available in the text.